SECRETORY EXPRESSION OF CA15-3 LIKE RECOMBINANT ANTIGEN IN MAMMALIAN CELLS - ANUJ KUMAR GUPTA,; PARVINDER KAUR,; SURYA SEHGAL,; PRANALI PATIL,; PARESH B. BHANUSHALI,; PRASHANT KHADKE,; MANOJ CHUGH, (International Journal of Pharma and Bio Sciences, 2015)
Breast cancer is most common life-threatening malignant lesion in women all over the world. Cancer antigen 15-3 (CA 15-3) is a widely used prognostic marker for breast cancer. CA 15-3 is a glycoprotein that is recognized with a match pair of DF3 and 115D8 monoclonal antibodies. DF3 antibody detects 8 amino acids sequence (DTRPAPGS) of tandem repeats in MUC1 protein, serves as a detection antibody in a sandwich assay while 115D8 monoclonal antibody binds to peptide- carbohydrates epitope on same repeat acts as the capture antibody in sandwich assay. In this study, we have developed a protein sequence containing 10 Tandem repeats with few approximate repeats out of MUC1 protein expressed in CHO-K1 cells to ensure post translational modifications. We have incorporated ‘Gluc’ protein (Gaussia luciferase) sequence along with gene of interest for secretion of protein outside the cells. Protein was characterized by western blot using CA15-3 antibody as well as confirmed for the presence of epitopes similar to the ones, as recognized by 115D8 and DF3 on Siemens CLIA based platform. Further validation studies are needed to demonstrate equivalence of the expressed protein with native purified CA15-3 protein to be used to develop diagnostic/prognostic tests.